92 The Association of Night-Time Systolic Blood Pressure with Ultrasound Markers of Subclinical Cardiac and Vascular Damage. (3rd June 2016) - O'Flynn, Anne Marie; Curtin, Ronan; Kearney, Patricia
Abstract : Background: Ambulatory blood pressure monitoring (ABPM) measures blood pressure (BP) over a prolonged period and has been shown to be superior to office BP for the prediction of clinical events. In particular, night-time systolic BP is a stronger predictor than systolic daytime BP. It is not yet clear if night-time BP should be a specific therapeutic target although some studies have demonstrated promising results. Subclinical cardiovascular disease is a prognostic marker for future cardiovascular events. Our aim is to examine the association of night-time systolic BP with subclinical cardiac dysfunction measured by global longitudinal strain (GLS) and subclinical vascular damage measured by carotid intima media thickness (CIMT) and carotid plaques. Methods: In 2014 a random sample of 80 individuals, stratified by BP status at baseline recruitment to the Mitchelstown Cohort Study, were invited to undergo repeat ABPM, echocardiogram and carotid ultrasound. ABPM was performed using the Spacelabs 90217 monitor. GLS was measured by speckle-tracking analysis of echocardiogram images carried out on a Philips iE33 ultrasound machine. Mean CIMT was measured at the distal 1 cm of the common carotid artery. Still images were taken from 3 angles on both sides of the neck using a Philips Cx50 ultrasound machine. The presence of carotid plaques was recorded. Philips QLAB cardiac and vascular ultrasound quantification software was used for analysis. The association of night-time systolic BP with GLS, CIMT and carotid plaques was assessed using linear and logistic regression. Results: Fifty (response rate 63%) individuals took part in this study. In univariable models night-time systolic BP was significantly associated with GLS (Beta coefficient 0.85 for every 10 mmHg rise, 95% CI 0.3–1.4) and carotid plaques (OR 1.9 for every 10 mmHg rise, 95% CI 1.1–3.2). Univariable analysis of daytime systolic BP did not demonstrate any statistically significant associations. In age and sex adjusted models, the association for night-time systolic BP and GLS remained significant (Beta coefficient 0.7 for every 10 mmHg rise, 95% CI 0.1–1.3). The association for carotid plaques was no longer statistically significant. In multivariable models findings were diminished. Discussion: Our results support an association between night-time systolic BP and subclinical cardiac and vascular disease. However this is a small study which limits generalisability and the sample size may have provided insufficient power to detect true associations between night-time systolic BP and target organ damage in multivariable models and CIMT in particular. The use of ABPM and ultrasound technology may help guide therapeutic decisions in those with hypertension. When assessing ABPM results the absolute night-time BP seems to be the most important parameter but ultimately a large randomised controlled trial involving chronotherapy is necessary to fully address this.